Effect of sodic water irrigation on yield and cation composition of vetiver (Vetiveria zizanioides (L.) Nash.) - SINGH, ARUN PRASAD, DINESH KUMAR, D V (Journal of Spices and Aromatic Crops, 1999)
The effect of residual sodium carbonate in irrigation water on the yield and cation composition of vetiver (Vetiueria zizanioides) was studied in open bottom reinforced concrete cemented cylindrical barrels embedded in the field at Lucknow, India. While shoot and root yields of vetiver were not significantly affected with residual sodium carbonate in irrigation water, oil yield significantly decreased at the residual sodium carbonate concentration of 8 meP and above as compared to control (tube well water). The concentration of sodium was about 10 times higher in the root than in shoot tissues. The great ability of vetiver to limit sodium entry in shoot tissues and maintain sufficient potassiunl and calcium concentration at high residual sodium carbonate concentration indicate that it is a tblerant to sadie stress.